Understanding the Impact of the Sirtuin 1 (SIRT1) Gene on Age-related Macular Degeneration: A Comprehensive Study - Saranya Velmurugan; Rashmi Pauline; Gurudeva Chandrashekar; Langeswaran Kulanthaivel; Gowtham Kumar Subbaraj (Nigerian Postgraduate Medical Journal)
Age-related macular degeneration (AMD) is a prevalent and incurable condition affecting the central retina and posing a significant risk to vision, particularly in individuals over the age of 60. As the global population ages, the prevalence of AMD is expected to rise, leading to substantial socioeconomic impacts and increased healthcare costs. The disease manifests primarily in two forms, neovascular and non-neovascular, with genetic, environmental and lifestyle factors playing a pivotal role in disease susceptibility and progression. This review article involved conducting an extensive search across various databases, including Google Scholar, PubMed, Web of Science, ScienceDirect, Scopus and EMBASE, to compile relevant case–control studies and literature reviews from online published articles extracted using search terms related to the work. SIRT1, a key member of the sirtuin family, influences cellular processes such as ageing, metabolism, DNA repair and stress response. Its dysregulation is linked to retinal ageing and ocular conditions like AMD. This review discusses the role of SIRT1 in AMD pathology, its association with genetic variants and its potential as a biomarker, paving the way for targeted interventions and personalised treatment strategies. In addition, it highlights the findings of case–control studies investigating the relationship between SIRT1 gene polymorphisms and AMD risk. These studies collectively revealed a significant association between certain SIRT1 gene variants and AMD risk. Further studies with larger sample sizes are required to validate these findings. As the prevalence of AMD grows, understanding the role of SIRT1 and other biomarkers becomes increasingly vital for improving diagnosis, treatment and, ultimately, patient outcomes.